Analysis of the safety and efficacy of the self-pulling and latter transected technique in modified overlap anastomosis in total laparoscopic total gastrectomy - Wang, Jintian; Xiong, Jing; Wang, Pengcheng; Lin, Jianan; Zhong, Wenjin; Kang, Wengui; Wu, Chuying; Chen, Junxing; Zheng, Huida; Ye, Kai (Frontiers in Oncology, 2024)
Background Laparoscopic total gastrectomy plus lymph node dissection is an effective treatment method for patients with gastric cancer. With the development and popularization of laparoscopic techniques in recent years, surgeons have become more skilled in laparoscopic techniques. Totally laparoscopic total gastrectomy (TLTG) has been developed; however, digestive tract reconstruction remains difficult, especially with anastomosis of the esophagus and jejunum. Using the self-pulling and latter transection (SPLT) method combined with a linear stapler has effectively solved the problem of narrow space in esophagojejunostomy. Here, we examined the safety and effectiveness of the SPLT technique in TLTG compared with SPLT with traditional esophagojejunostomy overlap anastomosis. Methods We retrospectively analyzed all patients with gastric cancer admitted to the Department of Gastrointestinal Surgery of the Second Affiliated Hospital of Fujian Medical University from September 2020 to September 2023. In total, 158 patients met the inclusion criteria and were included. Patients were grouped according to whether the lower esophagus was transected after self-pulling. Patient demographics, tumor characteristics, surgical conditions, and postoperative results between the two groups were statistically analyzed. Results A total of 158 patients were included in the study. All patients underwent TLTG and completed intracavitary anastomosis. There were 70 cases (44%) in the SPLT-Overlap group and 88 cases (56%) in the traditional overlap group. There was no significant difference in demographic and oncological characteristics between the two groups. The operation time (P = 0.002) and esophageal jejunum anastomosis time (P<0.001) were significantly shorter in the SPLT-Overlap group compared with the traditional overlap group. The intraoperative blood loss of the SPLT-Overlap group was 80.29 ± 36.36 ml, and the intraoperative blood loss of the traditional overlap group was 101.40 ± 46.68 ml. The difference was statistically significant (P=0.003). The SPLT-Overlap group also achieved a higher upper cutting edge (P =0.03). There was no significant difference between the two groups in terms of the incision size, postoperative hospital stay, time to first flatus, time to first liquid intake, drainage tube removal time, and esophagojejunal anastomotic diameter. There were 15 and 19 cases of short-term postoperative complications in the SPLT-Overlap and traditional Overlap groups, respectively. All patients received R0 resection, and no secondary surgery or death occurred. Conclusion We applied SPLT to overlap anastomosis. Short-term, SPLT has good safety and feasibility in TLTG. It can effectively shorten the time of digestive tract reconstruction, simplify the reconstruction procedure, and make the digestive tract reconstruction simple and fast; at the same time, a safe cutting edge can be obtained.